Approximate boundary conditions in electromagnetics - Senior, Thomas B. A.; Volakis, J. L. (Institution of Electrical Engineers, 1995)
The following topics were dealt with: first-order conditions; planar structures; impedance wedges; second-order conditions; higher-order conditions; GIBC conditions to cylindrical bodies; absorbing boundary conditions; generalized Rytov analysis; and steepest descent method.